2015
DOI: 10.1093/molehr/gav019
|View full text |Cite
|
Sign up to set email alerts
|

Cell-penetrating peptides, targeting the regulation of store-operated channels, slow decay of the progesterone-induced [Ca2+]isignal in human sperm

Abstract: Previous work has provided evidence for involvement of store-operated channels (SOCs) in [Ca2+]i signalling of human sperm, including a contribution to the transient [Ca2+]i elevation that occurs upon activation of CatSper, a sperm-specific cation channel localized to the flagellum, by progesterone. To further investigate the potential involvement of SOCs in the generation of [Ca2+]i signals in human sperm, we have used cell-penetrating peptides containing the important basic sequence KIKKK, part of the STIM–O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Others have observed a biphasic response consisting of a maximal transient peak signal at ∼50–100 seconds followed by a rapid decay to a minimum at ∼150–250 seconds, followed by a lower level signal that was sustained for up to 800 seconds (Strunker et al, 2011; Brenker et al, 2018b ). The sustained component of the biphasic response is likely due to opening of store-operated channels, which promote calcium influx ( Morris et al, 2015 ). The longer-lived calcium response in our studies likely precluded observation of the low-level, sustained signal and was likely due to the following factors: (1) the use of probenecid to block dye efflux, (2) the use of centrifugation to prepare sperm instead of the “swim-up” method, (3) low pH/low K + buffer containing 0.2 mM Ca 2+ instead of human tubal fluid, and (4) the use of Pluronic F-127 to increase dye uptake by others (Strunker et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Others have observed a biphasic response consisting of a maximal transient peak signal at ∼50–100 seconds followed by a rapid decay to a minimum at ∼150–250 seconds, followed by a lower level signal that was sustained for up to 800 seconds (Strunker et al, 2011; Brenker et al, 2018b ). The sustained component of the biphasic response is likely due to opening of store-operated channels, which promote calcium influx ( Morris et al, 2015 ). The longer-lived calcium response in our studies likely precluded observation of the low-level, sustained signal and was likely due to the following factors: (1) the use of probenecid to block dye efflux, (2) the use of centrifugation to prepare sperm instead of the “swim-up” method, (3) low pH/low K + buffer containing 0.2 mM Ca 2+ instead of human tubal fluid, and (4) the use of Pluronic F-127 to increase dye uptake by others (Strunker et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that store-operated Ca 2+ channels can contribute to the nature of progesterone-mediated Ca 2+ signals in human sperm [26], and thus regulate their hyperactivation in the female reproductive tract [27;28]. Indeed, the testis expresses a number of calcium channels, including the testis-specific CATSPER, voltage-dependent Ca 2+ channels and Ca 2+ -permeable TRP channels [1].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, STIM and Orai proteins were documented in human ( 49 ) and mouse sperm ( 60 ) by Western blot and immunocytochemistry. Using cell-penetrating peptides attached to a protein domain that stimulates STIM–Orai activity, Morris et al ( 61 ) were able to induce store-operated Ca 2+ activity at the neck of human sperm, downstream of CatSper stimulation by progesterone. Thus, these findings strongly suggest that as with SPCA, this store-operated Ca 2+ entry complex is spatially separated from our observations of Ca 2+ increase located over the acrosome/apical-acrosome during ACR.…”
Section: Discussionmentioning
confidence: 99%